An Islamic Legal Analysis of the Assuro Ammaca Ritual at the Sawerigading Tomb in Pamatata Village Selayar Islands Indonesia (Program Studi Hukum Keluarga Islam, 2025)
This study examines the Assuro Ammaca ritual practiced at the Sawerigading tomb in Pamatata Village, Selayar Islands, from the perspective of Islamic law and local community beliefs. In various religious and cultural traditions, rituals inherited from ancestors function as moral and spiritual guidelines that shape community life. However, such practices often raise theological questions when they intersect with Islamic doctrines. This research aims to explore the meaning, process, and legal implications of Assuro Ammaca within the framework of Islamic law, and to understand how the local community perceives and maintains the ritual. This study employs a field-based qualitative research method, using observation, in-depth interviews, and documentation to collect data from community members, religious figures, and traditional leaders. The findings reveal that Assuro Ammaca at the Sawerigading tomb is understood by the community as an expression of gratitude and respect toward a spiritual entity believed to provide protection, blessings, and assistance in daily life. The ritual involves specific offerings and prayers that reflect a syncretic blend of ancestral beliefs and religious expressions. From the perspective of Islamic law, this practice raises significant theological concerns. Appealing to entities other than Allah for protection or blessings contradicts the principle of tawhid (monotheism, the oneness of Allah), the core of Islamic belief. While Islam recognizes local traditions (‘urf) as long as they do not conflict with Sharia principles, the Assuro Ammaca ritual demonstrates a deviation in matters of belief. Therefore, this practice cannot be justified within Islamic law, particularly in its theological dimension.